ENTREPRENEURSHIP EDUCATION FOR FIRST MIDDLE SCHOOL AGE CHILDREN - Kusumadewi, Ninik Tri; Wijanarko, Beny (Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, 2022)
Entrepreneurship education in Indonesia has received less attention from both the world of education and society. Basic Entrepreneurship Education must be instilled early on which can be applied starting from SD/MI or SMP/MTs. Entrepreneurship education aims to develop attitudes, souls and abilities to create something of value for oneself and others. Being creative, innovative, independent, leadership,good at managing money, and having an unyielding spirit are some of the entrepreneurial attitudes that need to be instilled in children from an early age. This needs to be instilled early on because the various economic challenges facing our country are getting tougher. These entrepreneurial values become important points in the formation of life skills in children. The formation of life skills is not only through family education, but entrepreneurship education can be implemented in an integrated manner with learning activities in school. Junior High School (SMP) students can be trained to develop entrepreneurial attitudes, souls and abilities through various creative activities that can be integrated with the applicable curriculum. Various strategies and methods that can be used by teachers to cultivate good values from the character of a successful entrepreneur. Entrepreneurship education taugh since junior high school is expected to be able to reduce consumptive patterns in children by training them to create something of value and bring the next generation to create job in the future. So in this case, teachers and parents have an important role to play in developing children’s life skills and fostering interest and potential in children through entrepreneurship. This study aims to determine the model of entrepreneurship education at SMP Negeri 3 Leksono District, Wonosobo Regency. This research with a qualitative approach. Data collection techniques using observation techniques, interviews and documentation. Data analysis techniques by reducing data, presenting data, drawing conclusions and verification. The results of this study indicate that (1) the implementation of entrepreneurship education at Leksono 3 Public Middle School by incorporating entrepreneurial character is integrated into learning. The characters instilled in students are leadership, responsibility, discipline, creative, innovative, dare to take risks, work hard, cooperate and be communicative; (2) the evaluation of the entrepreneurship education model at SMP Negeri 3 Leksono is carried out by direct practice in the field starting from planning, spending, production, marketing, to preparing reports; (3) the inhibiting factors are children who have not discovered their talents and lack of support from parents.